Suppression of the TGF‐β1‐induced protein expression of SNAI1 and N‐cadherin by miR‐199a. (10th July 2014) - Suzuki, Toshihiro; Mizutani, Kiyohito; Minami, Akihiro; Nobutani, Kentaro; Kurita, Souichi; Nagino, Masato; Shimono, Yohei; Takai, Yoshimi
<x xml:space="preserve">Abstract</x> MicroRNA miR‐199a is clustered with miR‐214 on chromosome 1 and its expression is up‐regulated by various factors that are associated with epithelial‐to‐mesenchymal transition (EMT), such as a transcriptional repressor Twist1 and transforming growth factor (TGF)‐β. miR‐199a is either up‐regulated or down‐regulated in a variety of cancers, although EMT is associated with the progression of cancer. We found here that miR‐199a suppressed the translation of SNAI1, a transcriptional repressor that plays a role in EMT, by targeting the sequence within the 3′UTR of the SNAI1 mRNA, and reduced the protein level of SNAI1. miR‐199a increased the protein level of claudin‐1 in both the TGF‐β1‐treated and ‐untreated cells at least partly by decreasing the protein level of SNAI1, a transcriptional repressor for claudin‐1. In addition, miR‐199a targeted the sequence within the 3′UTR of the N‐cadherin mRNA and suppressed the TGF‐β1‐induced increase in the protein level of N‐cadherin in a manner independent of SNAI1. These results indicate that miR‐199a suppresses the TGF‐β1‐induced protein expression of SNAI1 and N‐cadherin.